‘In the Land of Dreams’: Carl Nielsen’s Second Thoughts about Wagner - Staugaard Villagomez, Nanna (Danish Yearbook of Musicology, 2021)
The article investigates Carl Nielsen’s views on Richard Wagner in order to understand what might have driven him to discard one of his own songs, ‘In the Land of Dreams’ (‘I Drømmenes Land’), for having a Wagnerian sentiment. Nielsen’s varying opinions of Wagner are accounted for as well as Nielsen’s understanding of the nature of music. Based on these statements, a musical analysis of ‘In the Land of Dreams’ focuses on discovering and pointing out similarities between Nielsen’s idea of Wagner’s musical style and specific musical features in the song. Possible reasons behind Nielsen’s changing points of view are discussed, including to which extent Danish society could be said to have influenced and encouraged the discourse of Nielsen as anti-Wagner. It is concluded that both Nielsen and Danish society had multiple reasons for wanting to separate Nielsen from Wagner, such as Nielsen’s personal ambition to make a name for himself as a composer and Denmark’s need of a national hero, which only grew stronger following the German occupation. However, because of these agendas, the differences between Nielsen and Wagner have tended to be exaggerated as they do in fact share more musical ideals than one might assume, including a desire to liberate music’s own inner will through alternative harmonic approaches and an aversion for musical sentimentality and programme music.